PERANCANGAN SISTEM INFORMASI INVENTARIS BARANG PADA HOTEL CITY VIEW SORONG - Melda Agnes Manuhutu (LPPM Poltek ST Paul, 2022)
Hotel City View Sorong is one of the hotels located in the City of Sorong area, In the service that has been running so far, Hotel City View Sorong opens services every day at a specified time, while the process of collecting data for goods is done manually, hotel employees must collect data on goods do the ledger. Based on the condition of the manual, the identification of the problem obtained is fully carried out still using human resources which allows for errors in the process of entering goods. In this study, the data collection method used observation, interviews and using the prototype method to develop the system. The website is prepared with a development stage procedure that includes an analysis of user needs, then implementation using PHP as the PHP programming language and MySql as the database. System testing by doing Black Box testing. From the research conducted, a warehouse inventory system software is produced with the ability to find out the amount of stock items and store data on incoming and outgoing goods and control warehouse inventory.